Absorption spectra of layered ZnI₂ and K₂ZnI₄ compounds intercalated with CO₂ - Yunakova, O.N.; Miloslavsky, V.K.; Kovalenko, E.N.; Makovetsky, E.D. (Functional Materials, 2009)
The absorption spectra of thin films of ZnI₂ and K₂ZnI₄ layered compounds intercalated with CO₂ molecules have been investigated in temperature interval from 90 to 240 K. It is found that the intercalation results in high-frequency shift of exciton bands and their broadening. Considering the structure of ZnI₂ and K₂ZnI₄ crystal lattices, the most probable positions of CO₂ molecules in spacings between layers of compounds have been established. It is shown that, in K₂ZnI₄ compound, unlike ZnI₂, there are two position types of intercalant molecules with molecular axes of different orientation relative to the compound crystallographic axes. Досліджено спектри поглинання тонких плівок шаруватих сполук ZnI₂ та K₂ZnI₄, интеркальованих молекулами CO₂, у температурному інтервалі від 90 до 240 К. Виявлено, що інтеркаляція спричиняє високочастотний зсув екситонних смуг та їх розширення. Шляхом розгляду структур кристалічних граток ZnI₂ та K₂ZnI₄ визначено найімовірніші положення молекул CO₂ у міжшарових проміжках сполук. Показано, що, на відміну від ZnI₂, в K₂ZnI₄ існують два типи положень інтеркальованих молекул з різними орієнтаціями молекулярних осей відносно кристалографічних осей сполуки. Исследованы спектры поглощения тонких пленок слоистых соединений Znl2 и K₂ZnI₄, интеркалированных молекулами CO₂, в температурном интервале от 90 до 240 К. Обнаружено, что интеркаляция приводит к высокочастотному смещению экситонных полос и их расширению. Путем рассмотрения структур кристаллических решеток Znl2 и K₂ZnI₄ определены наиболее вероятные положения молекул CO₂ в межслоевых промежутках соединений. Показано, что, в отличие от Znl2, в K₂ZnI₄ существуют два типа положений интеркалированных молекул с различными ориентациями молекулярных осей относительно кристаллографических осей соединения.